KOMUNIKASI INOVASI DALAM ADOPSI BENIH UNGGUL BARU TANAMAN PANGAN PADA KELOMPOK TANI DI KABUPATEN NAGAN RAYA: Communication on Innovation in Adoption of New Superior Seeds of Food Crops on Farmers’ Group in Nagan Raya Regency - Sarah Ridwan; Putri Maulina; Yuhdi Fahrimal (IPB University, 2022)
Superior seeds are one solution for improving agricultural production in Nagan Raya Regency. The main problem that occurs is the difficulty of adoption by farmers due to a lack of information regarding the benefits that will be obtained through superior seeds. Therefore, communication plays a role in the process of spreading ideas and technology so as to accelerate the process of agricultural modernization. This study aims to identify and explain the communication of innovations made between agricultural and food policymakers and farmers in Nagan Raya Regency. The method used in this research was descriptive qualitative by extracting information from agricultural policymakers in Nagan Raya Regency consisting of farmer groups, agricultural extension workers, and employees of the Department of Agriculture and Livestock in Nagan Raya Regency. The results showed that superior seed innovation in Nagan Raya Regency still focused on three types, namely, Rice, Corn, and Soybeans (Pajale) which were imported from outside the region because there were not enough supporting resources for developing superior seeds independently in Nagan Raya Regency. The communication process carried out by agricultural policymakers in disseminating superior seeds to farmer groups includes (1) introduction of target audiences based on demographic aspects and socio-economic status of farmers; (2) designing messages that are appropriate to the target group's target audience; (3) determination of methods and techniques using comparative study methods, demonstration plots, and demonstration plots; and (4) selection of communication channels that are limited to face-to-face communication and limited use of audio-visual media. ABSTRAKBenih unggul merupakan salah satu solusi bagi perbaikan produksi pertanian di Kabupaten Nagan Raya. Permasalahan utama yang terjadi adalah sulitnya adopsi dilakukan oleh petani karena kurangnya informasi terkait manfaat yang akan didapatkan melalui benih unggul. Oleh karenanya komunikasi berperan dalam proses penyebaran ide dan teknologi sehingga mempercepat proses modernisasi pertanian. Penelitian ini bertujuan untuk menemukenali dan menjelaskan komunikasi inovasi yang dilakukan antara pemangku kebijakan pertanian dan pangan dengan petani di Kabupaten Nagan Raya. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan menggali informasi dari pemangku kebijakan bidang pertanian di Kabupaten Nagan Raya yang terdiri atas kelompok tani, penyuluh pertanian, pegawai Dinas Pertanian dan Peternakan Kabupaten Nagan Raya. Hasil penelitian menunjukkan bahwa inovasi benih unggul di Kabupaten Nagan Raya masih berfokus pada tiga jenis komoditas, yaitu, Padi, Jagung, dan Kedelai (Pajale) yang didatangkan dari luar daerah karena belum cukupnya sumber daya pendukung pengembangan benih unggul secara mandiri di Kabupaten Nagan Raya. Proses komunikasi yang dilakukan oleh pemangku kebijakan bidang pertanian dalam mensosialisasikan benih unggul kepada kelompok tani meliputi (1) pengenalan khalayak sasaran berdasarkan aspek demografis dan status sosio-ekonomi petani; (2) merancang pesan yang sesuai dengan target kelompok sasaran; (3) penetapan metode dan teknik yang menggunakan metode studi banding, demplot, dan demfarm; dan (4) pemilihan saluran komunikasi yang terbatas pada komunikasi tatap muka dan penggunaan media audio-visual secara terbatas.